Enhancing Marine Pilot Team Performance through Competence, Work Environment, and Operational Leadership - Arifin Arifin; Emeralda Ayu Kusuma (LifeSciFi, 2026)
Marine pilotage is a safety-critical port operation that requires effective coordination among competent personnel, supportive working conditions, and operational leadership to ensure safe, timely, and reliable vessel movements. This study aims to examine the effects of competence and work environment on marine pilot team performance and to investigate the mediating role of operational leadership. A quantitative explanatory design was employed using a census of 55 personnel involved in the marine pilot work system at Semen Indonesia Tuban Port. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results indicate that competence, work environment, and operational leadership each have a positive and significant effect on marine pilot team performance. Furthermore, operational leadership serves as a partial mediator, strengthening the effects of competence and work environment on team performance while maintaining significant direct relationships. These findings demonstrate that reliable pilotage performance depends not only on competent personnel and supportive operational conditions but also on effective operational leadership that translates these resources into coordinated, safe, and efficient operational execution.